Antioxidant and Signal-Modulating Effects of Brown Seaweed-Derived Compounds against Oxidative Stress-Associated Pathology. (12th July 2021) - Begum, Rahima; Howlader, Saurav; Mamun-Or-Rashid, A. N. M.; Rafiquzzaman, S. M.; Ashraf, Ghulam Md; Albadrani, Ghadeer M.; Sayed, Amany A.; Peluso, Ilaria; Abdel-Daim, Mohamed M.; Uddin, Md. Sahab
Abstract : The biological and therapeutic properties of seaweeds have already been well known. Several studies showed that among the various natural marine sources of antioxidants, seaweeds have become a potential source of antioxidants because of their bioactive compounds. Most of the metabolic diseases are caused by oxidative stress. It is very well known that antioxidants have a pivotal role in the treatment of those diseases. Recent researches have revealed the potential activity of seaweeds as complementary medicine, which have therapeutic properties for health and disease management. Among the seaweeds, brown seaweeds (Phaeophyta) and their derived bioactive substances showed excellent antioxidant properties than other seaweeds. This review focuses on brown seaweeds and their derived major bioactive compounds such as sulfated polysaccharide, polyphenol, carotenoid, and sterol antioxidant effects and molecular mechanisms in the case of the oxidative stress-originated disease. Antioxidants have a potential role in the modification of stress-induced signaling pathways along with the activation of the oxidative defensive pathways. This review would help to provide the basis for further studies to researchers on the potential antioxidant role in the field of medical health care and future drug development.